Fabrication of Diamond Membranes by Femtosecond Laser Ablation for MEMS Sensor Applications - Johann Zehetner; Alexander Kromka; Tibor Izsák; Gabriel Vanko; Lenka Gajdošová; Stephan Kasemann (Proceedings, 2020)
We present the feasibility in fabricating membranes and cantilevers made of diamond grown on Si/SiO2 substrates by femtosecond laser ablation. In the ablation process, we generated nano- and microstructures on the membrane surface. Such laser-induced periodic surface structures (LIPSS) are useful in tailoring the surface chemistry. In combination with wet or reactive ion etching, smooth membranes were generated.